MODEL TATA KELOLA DIGITAL TERPADU (MTGDT): SINTESIS KONSEPTUAL UNTUK PENGUATAN IMPLEMENTASI SISTEM PEMERINTAHAN BERBASIS ELEKTRONIK DI PEMERINTAHAN DAERAH - Jorry Karim (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2026)
Digital government transformation has become a strategic imperative in the era of the fourth industrial revolution. This study aims to develop an Integrated Digital Governance Model through systematic synthesis of existing digital governance frameworks to strengthen the implementation of the Electronic-Based Government System in Indonesian local governments, with a focus on Gorontalo City and Province. Using a conceptual study approach based on a systematic literature review of 30 reputable sources, this study finds that existing models have limitations in accommodating the context of local governments in developing countries. The resulting MTGDT encompasses seven integrated dimensions digital infrastructure, data governance, integrated digital services, digital HR capacity, regulatory framework, multi-stakeholder collaboration, and digital security and trust consistently oriented toward digital public value as the model's core. This study contributes to digital governance theory and practice by offering a contextual, measurable, and operationaliza ble model for SPBE strengthening in local governments.